PENGARUH PEMBINAAN DISIPLIN DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR TARUNA BALAI PENDIDIKAN DAN PELATIHAN ILMU PELAYARAN (BP2IP) TANGERANG - Nugroho, Rosalendro Eddy; Sami‟a, Waode (Sains Manajemen, 2016)
The purpose of this study was to determine the effect of coaching discipline and motivation toward learning achievement cadets Merchant marine Education and Training Institute ( BP2IP ) Tangerang . Respondents are cadets Merchant marine Education and Training Institute ( BP2IP ) Tangerang Youth fifty nine . The method used is distributing .questionnaires to cadets by using Likert scale . Analysis of data using multiple regressionmodels with SPSS . Partial regression analysis found that the variable coaching discipline significantly influence the motivation to learn , and each of the variables showed significant influence on the learning achievement of the Youth cadets Merchant marine Education and Training Institute ( BP2IP ) Tangerang . These results indicate that there is a simultaneous effect between variables influence the development of discipline andmotivation toward learning achievement cadets Merchant marine Education and Training Institute ( BP2IP ) Tangerang.